SHORTENING DISTANCES: SCIENCE AND ART/THEORY AND PRACTICES - Astrid Eggert Boehs (Universidade Federal do Paraná, 1998)
A reflection is offered on art,science,and the dichotomy between nursing theory and practice. As a startting point, canadian scholar JOY JOHNSONN's ideas are employed, on which she debates on nursing as art and and as science. An effort is made to uphold art as prctice, employing the term within a rational view supported by scientific knowledge. The need to work out nursing assistance practical problems is fought for, by using research and scientific knowledge as a possibilty to unite art or practice with science.